1996
DOI: 10.1108/02656719610108279
|View full text |Cite
|
Sign up to set email alerts
|

Implementing total quality management

Abstract: Describes the results of a survey in manufacturing, distribution and service organizations concerning total quality management (TQM). These results proved that an effective TQM programme should contain consistent training of all employees; significant improvement in communication between departments; and development of the standards to measure and control the cost of quality. Based on the survey results, identifies quantitative relationships between quality improvement characteristics and different internal fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Finally, managers reported that the leaders (managers) were less likely to practice TQM principles than the organisations' followers (employees). Radovilsky et al (1996) attempted to determine where companies experienced difficulties in implementing TQM programmes. The survey results revealed that 75.5 per cent of the respondents perceived their TQM programmes as good or excellent in terms of quality improvement, while the remainder evaluated their programmes as fair or poor.…”
Section: Challenging Nature Of Quality Implementationmentioning
confidence: 99%
“…Finally, managers reported that the leaders (managers) were less likely to practice TQM principles than the organisations' followers (employees). Radovilsky et al (1996) attempted to determine where companies experienced difficulties in implementing TQM programmes. The survey results revealed that 75.5 per cent of the respondents perceived their TQM programmes as good or excellent in terms of quality improvement, while the remainder evaluated their programmes as fair or poor.…”
Section: Challenging Nature Of Quality Implementationmentioning
confidence: 99%
“…Other impediments to the success of TQM were named, including the competitiveness of the market, workers with unproductive attitudes and incompetent fi eld managers. Several authors report other problems in TQM implementation: low quality standards (Gitlow, 1990) , failure to measure quality (Baltz, 1992, Rategan, 1992 , lack of incentives for employees consistently to provide quality goods and services (Papa, 1993) , and insuffi cient commitment by management to implementing quality (Maul and Gillard, 1993) (Radovilsky et al ., 1996) .…”
Section: Quality As ' Quick Fix ' or Integrated Long Term Plan?mentioning
confidence: 99%
“…[10]). Failure rates of up to 70% or 80% are mentioned [11]. Obviously this has generated a lot of research into the reasons for failure or success and solutions to overcome problems.…”
Section: Theories On CI Implementationmentioning
confidence: 99%
“…Some researchers have identified exogenous, i.e. contingency, factors that influence the implementation process and outcomes [11,12]. Examples include:…”
Section: Theories On CI Implementationmentioning
confidence: 99%